Navigating the Era of the Feeling Economy: Labor Market Shifts, Industrial Structure Transformations, and Strategic Policy Interventions - Sicong Hua; Lianqin Huang; Yibo Huang; Yulin Gong (Journal of World Economy, 2025)
Against the backdrop of the rapid development of AI, this study delves into how the “Feeling Economy” reshapes the labor market, industries, and consumer markets, and what challenges it brings. The main results highlight that the labor market is evolving from a “Thinking Economy” to a “Feeling Economy”. Demand for data analysis and basic computation is decreasing, while high-cognitive tasks are on the rise. This shift transforms industries via human-AI collaboration, hyper-personalization, and emotional branding. Consumer markets increasingly prioritize emotional connections. Nevertheless, challenges such as structural unemployment and data privacy issues surface. Thus, the government should conduct skills training, safeguard privacy, and regulate AI, and suppliers should enhance emotional value.